Business models for active buildings - Elliott,T; Geske,J; Green,R (Energies, 2022)
Active Buildings that allow users to adjust their demands on the grid to the needs of the energy system could greatly assist the transition to net zero, but will not be widely adopted unless the businesses involved can make money from doing so. We describe the construction, flexibility and information supply chains of activities needed to make these buildings work. Drawing on the results of an expert workshop, we set out four possible business models deserving further investigation. Developers may find it profitable to build or upgrade energy-efficient buildings with the monitoring and control equipment needed to adjust demand and energy storage as required, selling them soon after completion. Aggregators monitor the state of the building and communicate with the energy system to adjust the building’s demand while maintaining comfort levels, in return for suitable payments. Energy service companies may sell energy-as-a-service and own the equipment instead of a consumer who wishes to minimize their upfront costs, and the idea of an active, energy-efficient, building may be attractive to the tenants of the new group of all-inclusive rental companies, and hence to those companies. Our discussion shows that each is an evolution of an existing (successful) business model, but that further work will be needed to evaluate their profitability when applied to Active Buildings.